Global Bibliometric Review of Patient-Centered Care in Intensive Care Units: Management Perspectives, Gaps, and Future Directions - Heru Susilo; Elsye Maria Rosa (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Patient-Centered Care (PCC) has increasingly gained attention as an essential approach to improving the quality of care in Intensive Care Units (ICUs), where complex clinical conditions, rapid decision-making, communication barriers, and ethical challenges may hinder patient and family involvement. This study aims to examine the development of PCC research in ICU settings, identify dominant research themes and influential contributors, and formulate future research directions to support PCC integration into intensive care practice. A bibliometric analysis was conducted using Scopus-indexed publications from 2015 to 2024. The search identified 605 publications, which were screened and refined to 163 relevant articles from 70 journals, 42 countries, and 165 institutions. The findings reveal an overall increase in publications and four major thematic clusters: communication and family involvement, patient safety and quality of care, the role of healthcare professionals, and critical conditions and hospital mortality. The literature also shows a shift from clinically and safety-oriented concerns toward more comprehensive approaches emphasizing communication, shared decision-making, family participation, and individualized care. In conclusion, PCC research in ICUs is increasingly multidimensional and human-centered. Future research should focus on systematic PCC implementation, organizational barriers, family involvement, and vulnerable populations, particularly neonatal and pediatric patients.